A importância da implantação de programas sociais de castração de felinos: o que os tutores e veterinários sabem a respeito da relação da reprodução desses animais com a saúde pública e o que tem sido feito? - Silva, Débora Cristina Basílio Crispim da (2020)
Felines are increasingly conquering modern homes and it is up to veterinarians to be updated on the treatment of these animals to meet the needs of this type of public. Knowing the profile of tutors in the region where you work is essential to direct the performance of these professionals. This study had as main objective to evaluate the perception of cat guardians taken voluntarily to a project of social castration in the city of João Pessoa-PB about the reproductive characteristics of the species and it relation with the zoonosis control as well as to evaluate the conduct of orientation of veterinarians in the region regarding the reproductive management of these animals. Answers to virtual questionnaires applied to 326 tutors and 47 veterinarians were evaluated. Most tutors had a higher education level, received between one and three minimum wages (limiting factor for the preoperative evaluation of the animals) and were well informed about the risks of using contraceptive medications, advantages of indoor breeding, importance of population control for disease prevention and well- being. However, as to the risks of spaying during heat, early spaying and post- spaying behavior, they were little informed. The animals were mostly females from the street aged between two months and a year. The veterinarians were up-to-date on the feline reproductive particularities and their relationship with public health, they clarified their clients on the subject but most believed that heat prevents them from performing castration. They were also inclined to develop similar projects in their locations.